PENINGKATAN PENGETAHUAN DAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI MELALUI EDUKASI INTERAKTIF DI SMP NEGERI 5 SUKOHARJO - Rahman, Aditya Aulia; Wicaksono, Aliansi; Azzahra, Annisa; Zahro, Astrida Septi Berliana; Mar’atunsoalihah; Bhisma Murti (CV. Kalimasada Group, 2025)
Adolescents are a vulnerable age group when it comes to reproductive health issues due to rapid physical, emotional, and social changes, as well as a lack of accurate information. This community service activity aims to improve adolescents' knowledge and attitudes toward reproductive health through interactive education at SMP Negeri 5 Sukoharjo, Central Java. The method used was a quasi-experiment with a one-group pretest-posttest design involving 60 eighth-grade students selected purposively. The intervention was carried out through material delivery, discussions, question-and-answer sessions, and interactive quizzes for 120 minutes. The results showed a significant increase in the average knowledge score from 5.45 to 7.90 and the attitude score from 14.88 to 17.43 (p < 0.001). This indicates that interactive education is effective in increasing knowledge and shaping positive attitudes among adolescents towards reproductive health. This activity emphasizes the importance of applying interactive learning methods in schools as a promotional-preventive effort in addressing adolescent reproductive health issues.